Pelatihan Tari Kreasi Meusare- sare di SMP Negeri 8 Banda Aceh - Yeni Zuryaningsih; Cut Zuriana (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2025)
The objective of this community service activity is to facilitate the development of students' talents and interests in dance art. In addition to demonstrating proficiency in existing dance forms, students are expected to demonstrate the capacity to create original dance compositions inspired by local traditions. It is therefore essential to enhance the creativity of students in order to facilitate the development of their cognitive, psychomotor and affective abilities in alignment with the requirements of the curriculum. The Meusare creation dance training programme was conducted over a three-day period, from 9 am to 11 am, utilising a demonstration approach that integrated lecturers and students in the practice of diverse movement techniques. The dancers participating in the programme are students who have demonstrated aptitude and interest in the field of dance. The group comprises 10 women and 10 men. As a consequence of this training, the students were able to perform the Meusare-sare with their group, in a simple stage setting in front of the principal, the board of teachers, and all students at the school. The students' performance is the result of training in the form of PBL and can be appreciated by the school and other parties, thus ensuring the continuity and utility of this service.